Isotopic (S-O-Sr) constraints on the evolution of the barite-polymetallic system in the Colipilli district, Neuquén Basin (Argentina) - Melisa A. Salvioli; María F. Lajoinie; Clemente Recio; Ana L. Rainoldi; Hernán G. de la Cal; Mabel E. Lanfranchini; Nora N. Cesaretti (Journal of South American Earth Sciences, 2026)

Residual beachrock and coastal eolianite patches without anthropogenic components on the eastern coast of Cantabria (Spain) - Javier Elorza; Clemente Recio (Sedimentary Geology, 2025)

Contemporary beachrock formation at Arrigunaga beach (Bizkaia, Spain) on anthropogenic slag - Javier Elorza; Clemente Recio (Journal of Iberian Geology, 2023)
The large, thick beachrock of Arrigunaga beach (Bizkaia, Spain) is unusual among beachrocks because of (a) Its location, at 43ºN latitude; (b) The substrate that was cemented, largely consisting on smelter slag mixed with natural beach sediment; (c) The timing and amount of slag dumping at sea, with millions of tons of waste dumped in the short interval AD 1902–1966; (d) The sudden cessation of dumping (AD 1966), followed by immediate beachrock exhumation and retrogradation and (e) An aggressive engineering intervention (AD 1999), supposedly aimed at beach regeneration, with imported bioclastic sands, resulting in additional weak cementation of the residual blocks. Thickness of the beachrock and the identification of internal clasts attest for a multiepisodic process with at least three main cementation steps and several CaCO 3 polymorphs precipitated from mixed marine and freshwaters. Evidence of bacterial remains suggests that biological activity helped to trigger cementation. C and O isotopic values obtained in the cements confirm the dominance of mixed marine and freshwaters composition. Exact knowledge of the start and finishing dates of slag dumping permits to tightly constrain the rapid cementation, which was already evident at least since AD 1924, that produced the beachrock, as well as its evolution towards its current fast and complete disappearance.

A Middle–Late Pleistocene palustrine–lacustrine–travertine system (Borj Edouane Unit, NW Tunisia): sedimentology, stable isotopes, and palaeohydrological implications - Naoufel Ghannem; Clemente Recio; Ildefonso Armenteros; Ramzi Azizi; Kamel Regaya (International Journal of Earth Sciences, 2020)

Contact metamorphism associated to the Penamacor–Monsanto granitic intrusion (Central Portugal): geochemical, isotopic and mineralogical features - Isabel Ribeiro da Costa; Isabel Margarida H. R. Antunes; Cyntia Mourão; Clemente Recio; Fernanda Guimarães; João Farinha Ramos; Fernando J. A. S. Barriga (Journal of Iberian Geology, 2018)

Pingüino In-bearing polymetallic vein deposit, Deseado Massif, Patagonia, Argentina: characteristics of mineralization and ore-forming fluids - Sebastián M. Jovic; Diego M. Guido; Isidoro B. Schalamuk; Francisco J. Ríos; Colombo C. G. Tassinari; Clemente Recio (Mineralium Deposita, 2011)

Source identification of sulphate forming salts on sandstones from monuments in Salamanca, Spain—a stable isotope approach - Nina Schleicher; Clemente Recio Hernández (Environmental Science and Pollution Research, 2010)